Normative Data for Multi-Dimensional Voice Program (MDVP) for Adults - A Computerized Voice Analysis System - Hema N.; Sangeetha Mahesh; Pushpavathi M. (Journal of All India Institute of Speech and Hearing, 2009)
Multi-Dimensional Voice Program (MDVP) is one of the instruments which provide the detailed acoustic analysis on all parameters. Among Western population many studies have been conducted to develop normative data across gender, dialect and language. The present study is aimed to develop norms for voice variable of MDVP in Indian population and compare same across western norms. Subjects considered were thirty male and thirty female normal subjects without any voice/communication disorders with age range of 18 to 25 years. MDVP- Computerized voice analysis (model 3950) system was used, voice parameters were displayed using Visi-Pitch IV hardware system. Voice sample was collected by asking subjects to phonate /a/ in their comfortable pitch and constant amplitude. The mean, standard deviation and the range (Indian norms) of MDVP is obtained using Independent t-test and is compared with the Western norms tosee the significant difference in the voice variables using one sample t-test. Difference is seen only in perturbation measurements. Comparison between genders has shown significant difference for few voice variables. The reason for increase in all the perturbation measurements of Indian norms would be due to difference in the vocal tract length, mass and tension. Factors like F0 level, phonatory initiation and termination also affects jitter magnitude in sustained phonation. More variation in amplitude perturbation may be due to room acoustics and microphone placement. Increment for soft phonation index may be due to the difference in manner of vowel phonation among the Indian and the Western population. Difference across the genders may be attributed to specific method of muscle excitation, laryngeal mucosal mechanism, sample size and higher Fo.These results can be attributed as norms which can be clinically used for the Indian population. It is apparent that measurement of acoustic variable has important application in diagnosis and treatment of voice disorders.